Energy saving analysis of the cooling plant using lake water source base on the optimized control strategy with set points change. (5th February 2018) - Ling, Li; Zhang, Quan; Yu, Yuebin; Ma, Xiaowei; Liao, Shuguang
Highlights: A cooling plant using lake water source was constructed. The optimized control strategy with set point change was obtained by using the energy optimization methodology. The cooling plant with the control strategy III achieved the energy savings of 33.1% over the control strategy I. The cooling plant with the control strategy III achieved the energy savings of 14.8% over the control strategy II. Abstract: A cooling plant using lake water source, combining free cooling technology and variable capacity technology, was constructed to remove the heat in data centers. This study explores the energy savings potential through energy optimization methodology considering the mutual effect of multi-variables set points on the performance of the entire cooling system compared to the reference control strategies with fixed set points (I and II). Because the lake water added one more dimension and resulted in a complex nonlinear problem, the energy optimization methodology using genetic algorithm was proposed. Based on the energy model of the cooling plant and genetic optimization, it is expected that the proposed control strategy can adapt to the variation of cooling load, thermal performance of the cooling plant, environmental conditions and drive the system toward a high overall energy efficiency. To evaluate the performance, we conducted a case study on a data center using Dongjiang lake water, in China, by comparing the strategy against method I and II. It was found that the cooling plant base on the control strategy III achieved the maximum energy savings of 33.1% over the control strategy I, and also obtained about 14.8% compared to the control strategy II.